2014
DOI: 10.1016/s1995-7645(14)60239-x
|View full text |Cite
|
Sign up to set email alerts
|

Screening and study of antifungal activity of leaf litter actinomycetes isolated from Ternate Island, Indonesia

Abstract: Ternate Island contains interesting biodiversity of actinomycetes that has potential use in agriculture, fisheries, and human health to reduce problem of fungal pathogen.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
0
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 15 publications
3
0
0
Order By: Relevance
“…The strong antimicrobial activity of EA-PB-52 was further confirmed by SEM studies which lead to morphological changes in the selected test microorganisms leading to shrinkage and cytosolic loss of the cells. These results are in conformity with the studies of Supaphon et al ( 2013 ) and Nurkanto and Julistiono ( 2014 ).…”
Section: Discussionsupporting
confidence: 93%
“…The strong antimicrobial activity of EA-PB-52 was further confirmed by SEM studies which lead to morphological changes in the selected test microorganisms leading to shrinkage and cytosolic loss of the cells. These results are in conformity with the studies of Supaphon et al ( 2013 ) and Nurkanto and Julistiono ( 2014 ).…”
Section: Discussionsupporting
confidence: 93%
“…This is the first report on its antibacterial activity against E. coli MTCC 40. SEM experiments further confirmed that the strong antimicrobial activity of EA-Kz-24 led to significant morphological changes in the selected test microorganisms leading to cell shrinkage and cytosolic loss. These results are in symmetry with the findings of Sharma et al 24 , Supaphon et al 77 , Nurkanto and Julistiono 78 .…”
Section: Discussionsupporting
confidence: 92%
“…The changes in morphology of yeast cells after treatment with Streptomyces sp. MN 2(6) are also consistent with findings of other researchers (Kitajima et al, 1976 ; Nurkanto and Julistiono, 2014 ). The shrinkage of cells was clearly observed in the electron micrograph which may be due to loss of cytosolic volume, which is mainly observed in case of polyene class of antibiotics (Kitajima et al, 1976 ).…”
Section: Discussionsupporting
confidence: 91%